Single Nucleotide Polymorphism of Partial GDF9 Gene in Three Local Goat of Indonesia Compare with Several Goat in Asia - Fatimah Az Zahra Chairunissa; Sigit Bintara; Tety Hartatik (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The GDF9 gene is a gene that affects the maturation of oocytes. GDF9 is expressed in oocytes and granulosa cell, it can stimulate granulose cell proliferation and regulate cumulus cell function from pre-ovulation to ovulation. The GDF9 gene is associated with an increase in the ovulation rate and litter size in animals. This study aims to determine the kinship relationship of local goats compared to goats in Asia on prolific traits and to determine the restriction mapping of the GDF9 gene in goats based on the different SNP locations. The local goat comes from the Bligon goat, Kacang goat and Kejobong goats which is compared to the GenBank data (EF446168, EU883989 and KY780296). GDF9 sequences were analyzed using BioEdit and sequencing results to identify Single Nucleotide Polymorphism (SNP) and using NEBCutter V2 to determine the restriction enzyme which recognized the sequence around SNP. The result shows that three variations of SNP were found in exon 2 (g.3615T>C, g.3760T>C and g.3855A>C). Identification of SNP position found 1 SNP position identified by restriction enzyme at g.3855A> C. The identified restriction enzyme is HpaII and MspI. The results of this study are expected to provide genetic information that will be used for further research on the relationship between GDF9 gene polymorphisms to animal prolific.